Avaliação do efeito do suco de uva orgânico como radiomodificador em modelos experimentais de radiobiologia - Freitas, Robson Borba de (2015)
The ionizing radiation exposure is able to affect the organic functions. The acute exposure produce several side effects as immunosuppression, gastrointestinal diseases, dermatitis and cardiac damage. Fractionated and localized exposure used for cancer therapy can be produced systemic side effects as anorexia and tissue necrosis. The present thesis shows two the results of two different models of radiobiology. The aim of the first study was to evaluate the radiomodifier effect in heart of black grape juice (BGJ) by animal model of acute radiation syndrome. Twenty rats were divided into four groups, two of them being irradiated by gamma-rays from a Co-60 source and two groups were sham-irradiated. Animals were treated by gavage with 2 mL per day of BGJ or placebo for one week before and 4 days after 6 Gy whole body gamma-irradiation. After euthanasia, the blood was collected for lactate dehydrogenase (LDH) quantification on serum and the hearts were excised and homogenized for lipid peroxidation measurement. High concentration of metabolites from lipid peroxidation in heart determined by reactive thiobarbituric acid reactive substances assay (TBARS), and high LDH level on serum were found only in gamma-irradiated group treated with placebo, mainly at the first 24 h after radiation. Phytochemical analysis of BGJ was performed by determining total phenolics, flavonoids, and tannins followed by a high-performance liquid chromatography (HPLC/DAD) analysis, which showed resveratrol (31.28 ± 0.04 mg/L) as the majority compound. Results suggest that BGJ is a good protective candidate compound against heart damage from ARS and its effects suggest its use as a radiomodifier. The second study investigated the secondary effects of fractionated whole brain irradiation (WBI). Radiotherapy is used for brain tumour treatment. WBI causes side effects such as neurocognitive impairments, anorexia and osteorradionecrosis. We used the BGJ as countermeasure to the side effects of WBI. Forty rats were exposed to 8 sessions of fractionated WBI. The total dose absorbed was 32 Gy. Forty rats were exposed to 8 sessions of fractionated WBI. The total dose absorbed was 32 Gy. The animals were divided into 4 groups equals to the studied groups in the first experiment. The rats received the BGJ or glucose and fructose solution 4 days before, during, and 4 days after WBI. Body weight, food and water consumption were measured during the experiment. The blood was collected 2 months after WBI and the mandibles were collected for morphometric and histological analysis. The irradiated and BGJ suplemented rats lost less weight than irradiated control rats (RG) in some days of WBI sessions, indicating a protective effect of BGJ. In some days, RJ rats ingested more food and water then RG rats. After WBI, all rats grew until day 61. Irradiated animals started losing weight again compared with controls as a consequence of mandibular osteoradionecrosis (ORN). Measurements performed on mandible showed that RG animals lost weight due to masticatory hypofunction. At microscopic level, osteoclastic activity and inflammation were apparent in mandibles of RG rats. Nevertheless, although BGJ did not completely restore the alterations induced by WBI, this antioxidant-rich beverage can be used to attenuate side effects of brain irradiation. In general, the BGJ offer protection to side effects induced by radiation in rats.